Forms of testaments in European legislatures - Vasiljković Jovana Z. (Institute of Comparative Law, Belgrade, 2021)
A testament is a unilateral legal act as it is made by a declaration of will of one person and is distinguished from other legal acts by its characteristics. By means of testament the testators may dispose of their rights and create an obligation for themselves and the obligations of the testament do not come into effect until after the death of the testator. A testament can be made in one of the forms prescribed by the law. The primary goal of this paper is to demonstrate and analyse different forms of testaments in the legislature of the Republic of Serbia and the chosen European legislatures of France, Germany, Italy and England. The following methods will be used in the paper: comparative analysis of the forms of testaments in the said legislatures, to be completed by the normative method, while by analysing the content in a systematic way we shall approach the subject matter, and the historical method, which will help us review the origin of certain forms of testaments.